Phase-Shift Method-Based Optical VSB Modulation Using High-Pass Hilbert Transform - K. I. Amila Sampath; Katsumi Takano (IEEE Photonics Journal)
This report presents a novel method of generating an optical vestigial sideband (VSB) modulated signal without using optical bandpass filters. Using a modified Hilbert transformer based on digital signal processing, an optical VSB-modulated signal is generated using the phase-shift method. The proposed method is demonstrated experimentally for an optical binary phase-shift keying (BPSK) signal. The proposed method is wavelength-transparent compared to an optical bandpass filtering method, where the wavelength dependence of the optical bandpass filter limits applications. Furthermore, the optical bandwidth of the modulated signal is readily adjustable by changing the cutoff frequency of the high-pass Hilbert transformer. Fiber transmission characteristics of a single-channel optical BPSK-VSB signal are analyzed using a 100-km transmission link. Results of fiber transmission analysis show tolerance of the proposed modulation scheme to fiber nonlinearity-based signal distortions. For a 10 Gbit/s non-return-to zero(NRZ) sequence, a self-phase modulation threshold of 13 dBm is reported for the studied system.